Analysis of the main economic factors and prices on the real estate market in Kazakhstan - Atabayeva, A.K.; Amirkulova, M.B.; Syzdykova, E.Zh.; Syzdykova, D.I. (BUKETOV BUSINESS REVIEW, 2018)
The article analyzes the influence of the main economic indicators of the real estate market in Kazakhstan, and a forecast of real estate prices. Since the real estate market refers to the resource market, then it affects all of the same factors that are characteristic of the resource market. It is not only the demand, supply, competition, the level of socially necessary labor, the industry average level of profitability, the state of the financial sector, the state level of intervention in terms of the functioning of the market, specific to the existence of market-based pricing mechanism. In accordance with its definition of the market value of the property depends on the factors that determine the average or more likely the price of its sale on the market in normal conditions of the transaction. Multivariate correlation and regression analysis for the period from 2007 to 2017 was conducted to assess the impact of the real estate market the main factors of development and forecast average annual data. As a result of the analysis obtained pairwise correlation coefficients, determining closeness of the relationship between variables. Along with the dynamics of the dollar for the analysis were chosen the most significant factors affecting the real estate market, such as the rate of the dollar to the tenge, the volume of mortgage lending; world oil prices, the nominal income residents. Determined closeness of the relationship between the studied factors. It revealed a level of correlation between the factors of the real estate market and selected the most relevant macroeconomic factors affecting the real estate market.